Developments in the analysis and design of marine structures : proceedings of the 8th International Conference on Marine Structures (Marstruct 2021, 7-9 June 2021, Trondheim, Norway) /: proceedings of the 8th International Conference on Marine Structures (Marstruct 2021, 7-9 June 2021, Trondheim, Norway). (2021) - Unknown
No abstract available